Modul Latihan Self-assessment: Media bagi Siswa Sekolah Menengah Atas untuk Tahap Awal Perencanaan Karier - Antika, Eni Rindi; Mappiare-AT, Andi; Zen, Ella Faridati (Jurnal Kajian Bimbingan dan Konseling, 2018)
In general, the particular research and development aimed to produce modules for students and guidebook modules for counselor which is acceptable both theoretically and practically. The acceptability is assessed in the terms of format or design, as well as the material content and practice. The developmental procedures adapted from Borg and Gall model, namely: (1) stage I preliminary study and planning, (2) stage II product development, (3) stage III product trial, (4) stage IV product revision, and (5) final product. The product was a Self-Assessment Training Module as a Career Stage Planning of Students in Senior High School and its guidebook. The results of product trials showed that the developed product had a “very good” acceptability score. In conclusion, the product is accepted both theoretically and practically. The acceptability of the product give implications that the using of Self-Assessment Training Module can help the students to recognize, assess, and understand themselves, and then they can plan their careers appropriately. The module can help the school counselor to guide students in self-assessment as the initial stage of career planning.